Natural preconditions for hiking in the Moldova River’s basin (Ukrainian Carpathian mountains) - Melnyk, Anatolij (Journal of Education, Health and Sport, 2017)
ThenaturalconditionsoftheMoldovaRiver’sbasininUkrainianCarpathiansaredescribed. The area hasgood perspectives for the development of hiking due to the slightly changed landscape complexes of the middle highland forests steep slopes and subalpine highland steep slopes with pine elfin woodlands and stones on the surface. The digital landscape maps of the basin showing lithology of the rocks, hypsometry, slopes, vertical stratification of climatic conditions, hydrographical network, and current vegetation cover were composed using the literature and cartographic sources. The attributes of the components of natural environment are described according the differentiation of the basin into its landscapes and altitude terrains.